Ring-alkyl connecting group effect on mesogenic properties of p-carborane derivatives and their hydrocarbon analogues - Jankowiak, Aleksandra; Kaszynski, Piotr; Tilford, William R.; Ohta, Kiminori; Januszko, Adam; Nagamine, Takashi; Endo, Yasuyuki (Beilstein Journal of Organic Chemistry, 2009)
The effect of the phenyl–alkyl connecting group on mesogenic properties of several series of isostructural compounds containing p-carborane (A and B), bicyclo[2.2.2]octane (C), and benzene (D) was investigated using thermal and optical methods. Results demonstrated that mesophase stability in the series containing A–D follows the order (Alk)CH2CH2– < (Alk)OOC– < (Alk)CH2O– < (Alk)COO–. Surprisingly, the connecting groups (Alk)CH2CH2– and (Alk)OOC– destabilize the mesophase significantly stronger for carboranes (A and B) than for carbocyclic derivatives (C and D). Analysis indicates that this effect may have quadrupolar and conformational origin.
Keywords: p-carborane; liquid crystals; structure-property relationship

(untitled) - Kaszynski, P.; Pakhomov, S.; Tesh, K. F.; Young, V. G., Jr (Inorg. Chem., 2001)

(untitled) - Kaszynski, P.; Januszko, A.; Ohta, K.; Nagamine, T.; Potaczek, P.; Young, V. G., Jr; Endo, Y. (Liq. Cryst., 2008)

(untitled) - Nagamine, T.; Januszko, A.; Ohta, K.; Kaszynski, P.; Endo, Y. (Liq. Cryst., 2005)

(untitled) - Nagamine, T.; Januszko, A.; Kaszynski, P.; Ohta, K.; Endo, Y. (J. Mater. Chem., 2006)

(untitled) - Nagamine, T.; Januszko, A.; Ohta, K.; Kaszynski, P.; Endo, Y. (Liq. Cryst., 2008)

(untitled) - Ohta, K.; Januszko, A.; Kaszynski, P.; Nagamine, T.; Sasnouski, G.; Endo, Y. (Liq. Cryst., 2004)

(untitled) - Piecek, W.; Kaufman, J. M.; Kaszynski, P. (Liq. Cryst., 2003)

(untitled) - Ringstrand, B.; Vroman, J.; Jensen, D.; Januszko, A.; Kaszynski, P.; Dziaduszek, J.; Drzewinski, W. (Liq. Cryst., 2005)

(untitled) - Douglass, A. G.; Czuprynski, K.; Mierzwa, M.; Kaszynski, P. (Chem. Mater., 1998)

Liquid Crystals: Chemistry and Structure - Douglass, A. G.; Mierzwa, M.; Kaszynski, P. (Liquid Crystals Containing p-Carborane, 1998)

(untitled) - Czuprynski, K.; Douglass, A. G.; Kaszynski, P.; Drzewinski, W. (Liq. Cryst., 1999)

(untitled) - Douglass, A. G.; Both, B.; Kaszynski, P. (J. Mater. Chem., 1999)

(untitled) - Czuprynski, K.; Kaszynski, P. (Liq. Cryst., 1999)

(untitled) - Douglass, A. G.; Czuprynski, K.; Mierzwa, M.; Kaszynski, P. (J. Mater. Chem., 1998)

(untitled) - Januszko, A.; Kaszynski, P.; Wand, M. D.; More, K. M.; Pakhomov, S.; O’Neill, M. (J. Mater. Chem., 2004)

(untitled) - Januszko, A.; Glab, K. L.; Kaszynski, P.; Patel, K.; Lewis, R. A.; Mehl, G. H.; Wand, M. D. (J. Mater. Chem., 2006)

(untitled) - Januszko, A.; Kaszynski, P.; Drzewinski, W. (J. Mater. Chem., 2006)

(untitled) - Januszko, A.; Kaszynski, P. (Liq. Cryst., 2008)

(untitled) - Januszko, A.; Glab, K. L.; Kaszynski, P. (Liq. Cryst., 2008)

(untitled) - Jasinski, M.; Jankowiak, A.; Januszko, A.; Bremer, M.; Pauluth, D.; Kaszynski, P. (Liq. Cryst., 2008)

(untitled) - Kaszynski, P.; Huang, J.; Jenkins, G. S.; Bairamov, K. A.; Lipiak, D. (Mol. Cryst. Liq. Cryst., 1995)

(untitled) - Kaszynski, P.; Douglass, A. G. (J. Organomet. Chem., 1999)

Anisotropic Organic Materials-Approaches to Polar Order - Kaszynski, P. (closo-Boranes as π Structural Elements for Advanced Anisotropic Materials, 2001)
and references therein

(untitled) - Villiger, A.; Leenhouts, F. (Mol. Cryst. Liq. Cryst., 1991)

(untitled) - Kaszynski, P.; Kulikiewicz, K. K.; Januszko, A.; Douglass, A. G.; Tilford, R. W.; Pakhomov, S.; Patel, M. K.; Ke, Y.; Radziszewski, G. J.; Young, V. G., Jr
submitted

(untitled) - Fox, M. A.; MacBride, J. A. H.; Peace, R. J.; Wade, K. (J. Chem. Soc., Dalton Trans., 1998)

(untitled) - Price, C. C.; Mueller, G. P. (J. Am. Chem. Soc., 1944)

(untitled) - Coult, R.; Fox, M. A.; Gill, W. R.; Herbertson, P. L.; McBride, J. A. H.; Wade, K. (J. Organomet. Chem., 1993)

(untitled) - Miyaura, N.; Yanagi, Y.; Suzuki, A. (Synth. Commun., 1981)

(untitled) - Chaumeil, H.; Le Drian, C.; Defoin, A. (Synthesis, 2002)

(untitled) - Sinclair, D. J.; Sherburn, M. S. (J. Org. Chem., 2005)

(untitled) - Tao, X.; Zhao, Y.; Shen, D. (Synlett, 2004)

(untitled) - Garrett, P. M.; Smart, J. C.; Hawthorne, M. F. (J. Am. Chem. Soc., 1969)

(untitled) - Mitsunobu, O. (Synthesis, 1981)

(untitled) - Leblanc, J. P.; Tessier, M.; Judas, D.; Friedrich, C.; Noël, C.; Maréchal, E. (Macromolecules, 1993)

(untitled) - Neubert, M. E.; Wildman, P. J.; Zawaski, M. J.; Hanlon, C. A.; Benyo, T. L.; De Vries, A. (Mol. Cryst. Liq. Cryst., 1987)

Textures of Liquid Crystals - Demus, D.; Richter, L. (VEB Deutscher Verlag für Grundstoffindustrie, 1980)

Smectic Liquid Crystals-Textures and Structures - Gray, G. W.; Goodby, J. W. G. (Leonard Hill, 1984)

Smectic Liquid Crystals Textures and Structures - Dierking, I. (Wiley-VCH, 2003)

(untitled) - Kelker, H.; Scheurle, B. (J. Phys. (Paris), 1969)

(untitled) - Neubert, M. E.; Stahl, M. E.; Cline, R. E. (Mol. Cryst. Liq. Cryst., 1982)

(untitled) - Onda, M.; Toda, A.; Mori, S.; Yamaguchi, I. (J. Mol. Struct., 1986)

(untitled) - Scharfenberg, P.; Rozsondai, B.; Hargittai, I. (Z. Naturforsch., A, 1980)

Structure and Bonding - Haase, W.; Athanassopoulou, M. A. (Crystal Structures of LC Mesogens, 1999)

Thermotropic Liquid Crystals - Toyne, K. J. (Liquid Crystal Behavior in Relation to Molecular Structure, 1987)

Handbook of Liquid Crystals - Demus, D. (Chemical Structure and Mesogenic Properties, 1998)

Selected Topics In Liquid Crystal Research - Demus, D.; Hauser, A. (Molecular structure and thermodynamic properties of nematic liquid crystals, 1990)

(untitled) - Vill, V.
Vill, V. LiqCryst 4.6 database (LCI Publisher GmbH, Hamburg, Germany, www.lci-publisher.com) and references therein.